Synthesis of high silica content silicoaluminophosphate-5 (SAPO-5) from non-aqueous medium using hexamethyleneimine template - Venkatathri, N (Journal of Scientific & Industrial Research, 2005)
Silicoaluminophosphate-5 (SAPO-5) molecular sieve with up to 2.4 Si atom per unit cell have been synthesized using hexamethyleneimine template in ethylene glycol medium (molar ratio of silica in the reaction gels up to 0.3). Crystallinity and silicon incorporation are confirmed by XRD, XRF, N, sorption study, TG/DTA, SEM. pyridine TPD technique and hydroxyl region FT-IR. These materials with high Si concentration show higher activity for toluene alkylation reaction than samples prepared with up to 0.1 molar ratio of silica in the gel of aqueous media.
Keywords: aqueous; FT-IR; hydroxyl region; non-aqueous; SAPO-5; SEM; TG/DTA; XRD